Decay Estimates for a Type of Fuzzy Viscoelastic Integro-Differential Model. (15th March 2021) - Zhang, Fengyun; Lin, Funing; Su, Guangwang; Xue, Guangming
Abstract : We consider a type of fuzzy viscoelastic integro-differential model in this paper. With the aid of some appropriate hypotheses, a unified method and the multiplier technique are implemented to get priori estimates precisely without constructing any auxiliary function. By establishing the estimation of energy function, we derive the stability result of the global solution, and we calculate the estimations of energy attenuation in exponential and polynomial forms, respectively.